Frequency upconversion, paramagnetic behavior and biocompatibility of Gd2O3:Er3+/Yb3+ nanorods - Singh S.; Kanika; Kedawat G.; Park J.H.; Ghorai B.; Ghorai U.K.; Upadhyay C.; Kaipparettu B.A.; Gupta B.K. (My University, 2025)
A facile base-catalyzed hydrothermal method is used to synthesize a bifunctional luminomagnetic Er3+/Yb3+ doped Gd2O3 nanorods material. The as-synthesized nanorods material is investigated for structural/microstructural, upconversion, and magnetic properties. The intense emission bands at 520 nm, 540 nm, and 654 nm are observed upon excitation with a 980 nm solid state laser. The effect of Yb3+, Er3+ doping concentrations and incident laser power on the upconversion emission properties are also investigated, and the mechanism for the upconversion process is proposed. We further investigated the magnetic properties by room temperature M-H and M-T measurements in the temperature range of 2-300 K by standard ZFC-FC protocols. Cytotoxicity analysis of these bifunctional luminomagnetic nanorods in established cell lines did not show considerable cytotoxicity. © 2021 The Author(s)